2007
DOI: 10.1002/pssb.200642588
|View full text |Cite
|
Sign up to set email alerts
|

Size‐selective excitation of biexcitons in CuCl quantum dots under two‐photon resonant excitation

Abstract: PACS 71. 78.55.Hx, 78.67.Hc Photoluminescence (PL) spectra of excitons and biexcitons confined in CuCl quantum dots have been measured under two-photon resonant excitation of the biexcitons in order to examine size-selective excitation of the biexcitons. Although the PL energy of the biexciton does not exhibit an obvious dependence on the excitation photon energy, the PL energy of the exciton clearly reveals the size of the quantum dots in which the biexcitons are generated under the two-photon resonant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…On the other hand, the M band does not show a peak energy shift even for size-selective excitation of biexcitons using an excitation pulse with a narrow spectral width [19]. From this result, we concluded that the M band is not originated from a free biexciton level which is directly excited by two-photon absorption process but originated from a certain level that exists on low energy side.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…On the other hand, the M band does not show a peak energy shift even for size-selective excitation of biexcitons using an excitation pulse with a narrow spectral width [19]. From this result, we concluded that the M band is not originated from a free biexciton level which is directly excited by two-photon absorption process but originated from a certain level that exists on low energy side.…”
Section: Resultsmentioning
confidence: 78%
“…From this result, we concluded that the M band is not originated from a free biexciton level which is directly excited by two-photon absorption process but originated from a certain level that exists on low energy side. Transition energy from free biexciton to exciton state depends on the dot size according to the two-photon excitation measurement [19] and transient absorption measurement [20]. Therefore, it is suggested that the origin of the FM band is a free biexciton state which is directly excited by the excitation pulse and that ultrafast radiation of superfluorescence in this experimental configuration results in the observation of the FM band before the free biexciton relaxes to an initial state of the M band.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we recently reported that the photon energy of M band is not equal to the absorption energy from the exciton to biexciton state [13]. Therefore, we consider that the M band is also a kind of bound state, such as surface-bound state inherent in the quantum dots.…”
Section: Resultsmentioning
confidence: 92%
“…Here we describe the size-selective excitation of biexcitons using direct two-photon resonant excitation [21]. Until now, two-photon resonant excitation of the biexcitons in the quantum structure has been used to identify biexciton luminescence in QDs and to clarify the biexciton binding energy [22][23][24].…”
Section: Size-selective Excitation Of Biexcitons Under Two-photon Res...mentioning
confidence: 99%